Doubly critical character of the N=90 isotones 150Nd, 152Sm, 154Gd, and 156Dy - Bonatsos, Dennis; Lenis, D.; Minkov, N.; Petrellis, D.; Yotov, P. (HNPS Advances in Nuclear Physics, 2019)
The N=90 isotones 150Nd, 152Sm, 154Gd, and 156Dy, which are known to provide the best examples of the X(5) critical point symmetry between quadrupole vibrations [U(5)] and axial quadrupole deformation [SU(3)], are proved to lie on the border between the regions of stable axial octupole deformation and octupole vibrations, described in terms of an Analytic Quadrupole Octupole Axially symmetric (AQOA) model including tunneling effects.